2022
DOI: 10.52965/001c.39580
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors and Associated Bleeding Risks: A Narrative and Clinical Review

Abstract: Major Depressive Disorder (MDD) is a major cause of disability worldwide and is associated with serious lasting impairment. A leading hypothesis of the pathophysiology of MDD is the monoamine deficiency hypothesis which suggests that depression is caused by depletion of serotonin, norepinephrine, or dopamine in the central nervous system. Serotonin is the most widely studied neurotransmitter in the pathophysiology of depression, with studies showing that reduced central serotonin synthesis leads to depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Many experimental and clinical studies have found a relationship between depressive disorders and serotonin deficiency in the brain [ 10 , 40 ]. Clinically effective antidepressants (for example, SSRI, selective serotonin reuptake inhibitors) increase the amount of serotonin available in the synapses [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental and clinical studies have found a relationship between depressive disorders and serotonin deficiency in the brain [ 10 , 40 ]. Clinically effective antidepressants (for example, SSRI, selective serotonin reuptake inhibitors) increase the amount of serotonin available in the synapses [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental and clinical studies have found a relationship between depressive disorders and serotonin deficiency in the brain [ 10 , 40 ]. Clinically effective antidepressants (for example, SSRI, selective serotonin reuptake inhibitors) increase the amount of serotonin available in the synapses [ 40 , 41 ]. We found that only CBA mice exposed to short-day conditions demonstrated decreased 5-HT and its metabolite 5-HIAA levels in the hypothalamus, a decreased 5-HT level in the hippocampus, and a reduced mRNA level of the Tph2 gene encoding the key enzyme for 5-HT biosynthesis in the midbrain [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be counseled on these risks. 7 Those prescribed lithium should use NSAIDs with caution due to the risk of developing lithium toxicity, and caffeine-containing products may lower lithium concentrations.…”
Section: Acute Treatmentsmentioning
confidence: 99%
“…Pregabalin's side effects include dizziness and drowsiness [42], and overuse can result in dependence [43]. Paroxetine may cause nausea, a dry mouth, and sexual dysfunction [44], with an increased risk of bleeding associated with overuse [45]. Citalopram can induce nausea and insomnia [46].…”
Section: Introductionmentioning
confidence: 99%